1992
DOI: 10.1128/jvi.66.7.4085-4097.1992
|View full text |Cite
|
Sign up to set email alerts
|

The surface envelope protein gene region of equine infectious anemia virus is not an important determinant of tropism in vitro

Abstract: Virulent, wild-type equine infectious anemia virus (EIAV) is restricted in one or more early steps in replication in equine skin fibroblast cells compared with cell culture-adapted virus, which is fully competent for replication in this cell type. We compared the sequences of wild-type EIAV and a full-length infectious proviral clone of the cell culture-adapted EIAV and found that the genomes were relatively well conserved with the exception of the envelope gene region, which showed extensive sequence differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
23
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 41 publications
(46 reference statements)
5
23
0
Order By: Relevance
“…WSU5 and Th.1 were found to replicate to high titers in all cells tested, whereas MA-1 replicated in the ED, UVEC and EREC cultures and the Wyoming strain of virus replicated only in macrophages. This limited cell tropism of the MA-1 and Wyoming strains had previously been reported (5,24). Thus, the macrovascular endothelial cell cultures support replication of the same viral strains as ED cells and produced similar levels of infectious virus as detected by TCIU assays.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…WSU5 and Th.1 were found to replicate to high titers in all cells tested, whereas MA-1 replicated in the ED, UVEC and EREC cultures and the Wyoming strain of virus replicated only in macrophages. This limited cell tropism of the MA-1 and Wyoming strains had previously been reported (5,24). Thus, the macrovascular endothelial cell cultures support replication of the same viral strains as ED cells and produced similar levels of infectious virus as detected by TCIU assays.…”
supporting
confidence: 75%
“…In tissue culture, EIAV has been found to replicate in equine monocyte-derived macrophages (14), equine fibroblasts (13,16), equine fetal kidney cells (4), and canine and feline fibroblast cell lines (4,13). Strains of virus previously grown in fibroblasts usually have a preference for replication in fibroblast and fibroblast cell lines, whereas strains obtained in vivo during a viremic episode or strains passaged in macrophages replicate to higher titers in primary equine macrophage cultures (5,24). Here we demonstrate for the first time that equine macrovascular endothelial cells are productively infected with EIAV.…”
mentioning
confidence: 99%
“…The nucleotide numbering refers to the position of each sequence with respect to the EIAV Pr proviral sequence. estingly, the EIAV PV and pony-derived LTRs lacked a second CAAT box motif and a third core ets binding motif that are present in the Wyoming and Th-1 LTRs (6,21,34). It has been suggested that two CAAT boxes and core ets binding motifs may be important in viral pathogenesis and replication in macrophages, respectively (6,21).…”
Section: Resultsmentioning
confidence: 99%
“…Ball et al (3) localized a principal neutralizing domain (PND) to the gp90 variable region, which accounts for the variable reactivity of different virus isolates to PND-specific, neutralizing monoclonal antibodies (14). Additional studies on EIAV sequence diversity have yielded similar results and have identi-fied a second highly variable segment of the genome within the U3 region of the long terminal repeat (LTR) (1,6,30,31,34).…”
mentioning
confidence: 99%
“…Pathogenesis research revealed that many of the clinical signs of disease were a result of widespread activation of the immune system McGuire et al, 1972). In the 1980's and 90's, biological and molecular clones of the virus have been developed by several researchers and the full nucleic acid sequence of many of these clones determined (Rushlow et al, 1986;Stephens et al, 1986;Yaniv et al, 1986;Kawakami et al, 1987;Whetter et al, 1990;Carpenter et al, 1991;Perry et al, 1992). A virulent molecular clone of the virus is now available, enabling research efforts to now be aimed at identification of specific molecular determinants of virulence (Fuller, unpublished data).…”
Section: Historical Overviewmentioning
confidence: 99%